Case Report: Getting a Peek at the Angle of a Patient with Severe Keratoconus - Kawashima, Rumi; Matsushita, Kenji; Ohnuma, Kazuhiko; Maeda, Naoyuki; Koh, Shizuka; Nishida, Kohji (Frontiers in Ophthalmology, 2022)
Visualization of the iridocorneal angle, which contains the aqueous humor circulatory system and controls intraocular pressure, is important for diagnosing and managing glaucoma; however, the presence of keratoconus, keratoglobus, or severe myopia may enable direct angle visualization without gonioscopy contact lenses or applying a coupling gel. We present the first report of a case in which the iridocorneal angle was viewed directly in an eye with keratoconus using the RetCam without applying gel to the cornea. This method overcame the inability to view the angle directly in a normal eye because of the total internal reflection.